Analysis of factors affecting Micro Small and Medium Enterprises using the marketplace in the New Normal - Najla Najmatul Fadhilah; Atiyah Fitri (Sekolah Tinggi Ekonomi Islam (STEI) SEBI, 2022)
This study aims to analyze the factors that influence the use of the marketplace by MSMEs in Tangerang City in facing the new normal seen from (1) knowledge (2) Trust (3) Motivation (4) Technology. The object of this research is the people of Tangerang City, while the sample of this research is MSME actors. The data used are primary data obtained from survey results by distributing questionnaires to 100 respondents in Tangerang City. The data analysis technique used in this study used the binary logistic regression method with a significance level of 5%. The results of this study show simultaneously knowledge, belief, motivation, and technology. Has an influence on the use of matketplace by MSMEs in Tangerang City. Meanwhile, partially only knowledge (0.001) and belief (0.009) have a significant effect. Other variables, motivation (0.128) and technology (0.369) did not significantly influence the use of the marketplace by MSMEs in the city of Tangerang in facing the new normal era. Binary Logistic Regression, Marketplace, MSMEs, Utilization